Bentuk-Bentuk Sesapa Dalam Pelaksanaan Ritual Saṃskāra Di Desa Pedawa Buleleng Bali - I Nyoman Suka Ardiyasa; Putu Maria Ratih Anggraini (Kamaya: Jurnal Ilmu Agama, 2021)
The use of Sesapa in carrying out religious rituals in Pedawa Village is the main thing, even though Hindus generally use Mantra as their language of worship. In Bali Aga Village, especially in Pedawa Village, the use of Sesapa or Balinese Dialect Pedawa has become the main language that cannot be replaced until now. This study questions the use of Sesapa in the implementation of religious rituals carried out in the Bali Aga Village. The method used in this research is descriptive qualitative. Data was collected by using interview and direct observation techniques. The results of this study indicate that the implementation cycle of Saṃskāra in Pedawa Village consists of (1) kayeh di cangkupe, (2) pungsed kepus (kepus puser), (3) nampi, (4) nampangang abulan pitung dina, (3) tiga bulanan, ( 4) ngotonin, (5) nyambutin, (6) nyrimpen, (7) pawiwahan, (8) metatah, (9) death ceremony and (10) ngangkid. While the form of greeting used by the people of Bali Aga Village is in the form of Balinese dialect Pedawa which is shown to the Gods, to the Ancestors, and to the Bhutas.